Hukum Menikahi Wanita Hamil Akibat Zina Menurut Abu Hanifah Dan Ibnu Hazm - Ahmad Faizal Adha (ISLAMICA, 2022)
Adultery is forbidden in Islam. Allah SWT. Give harsh punishments for the perpetrators, both unmarried and married. The punishment for those not married is to be lashed a hundred times and exiled. In contrast, the punishment for married people is stoning to death. With such a severe punishment, people who believe they can take care of themselves and stay away from all things that lead to adultery; however, with the massive development of technology and information and the proliferation of pornographic content easily accessible to young people today. In associations far from Islamic religious values, parental supervision is not complete because they are busy with their respective jobs and have disproportionate education about reproduction. Free Promiscuity has become an inevitable plague in today's modern life. It is proven by the number of young women who commit adultery until finally, many are pregnant out of wedlock. Dilemma hit the couple's family until many families from both sides agreed to hold marriage between the two. Pros and cons related to the law of marrying Pregnant women due to adultery are constantly repeated in society; the question that often arises is whether the marriage is legal or not? Abu Hanifah and Ibn Hazm were two well-known Islamic law thinkers in their time who also paid attention to this.